Feasibility of Genome-Scale Construction of Promoter::Reporter Gene Fusions for Expression in Caenorhabditis elegans Using a MultiSite Gateway Recombination System - Hope, Ian A.; Stevens, Jonathan; Garner, Anna; Hayes, Josie; Cheo, David L.; Brasch, Michael A.; Vidal, Marc (Genome Research, 2004)
The understanding of gene function increasingly requires the characterization of DNA segments containing promoters and their associated regulatory sequences. We describe a novel approach for linking multiple DNA segments, here applied to the generation of promoter::reporter fusions. Promoters from Caenorhabditis elegans genes were cloned using the MultiSite Gateway cloning technology. The capacity for using this system for efficient construction of chimeric genes was explored by constructing promoter::reporter gene fusions with a gfp reporter. The promoters were found to provide appropriate expression of GFP upon introduction into C. elegans, demonstrating that the short Gateway recombination site between the promoter and the reporter did not interfere with transcription or translation. The recombinational cloning involved in the Gateway system, which permits the highly efficient and precise transfer of DNA segments between plasmid vectors, makes this technology ideal for genomics research programs.